2018
DOI: 10.1590/0370-44672017710090
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of polystyrene using styrene-butadiene rubber (SBRr) waste from the shoe industry

Abstract: The vulcanized rubber waste from the shoe industry causes environmental damage when it is incinerated or inappropriately discarded, turning this into a problem of major concern. Therefore, this study had as the main objective the Polystyrene (PS) toughening using different contents of white vulcanized styrene-butadiene rubber (SBRr) waste produced in the shoe industry. The mixtures were initially prepared in a co-rotational double screw extruder and, thereafter, the extruded granules were injection molded. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
1
10
0
4
Order By: Relevance
“…As illustrated in Figure 2(a), pure PS showed a typical morphology of fracture surface of an amorphous polymer with no visible plastic deformation, indicating that the pure PS fractured in a brittle mode. 31 With the introduction of TPU into the PS matrix, sea island structure appeared in the PS/TPU blends and the interface between the PS phase and the TPU phase became distinct, indicating that the miscibility between the PS phase and the TPU phase was poor in the PS/TPU blends. This was consistent with the analysis of Cole–Cole plots in rheological properties.…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure 2(a), pure PS showed a typical morphology of fracture surface of an amorphous polymer with no visible plastic deformation, indicating that the pure PS fractured in a brittle mode. 31 With the introduction of TPU into the PS matrix, sea island structure appeared in the PS/TPU blends and the interface between the PS phase and the TPU phase became distinct, indicating that the miscibility between the PS phase and the TPU phase was poor in the PS/TPU blends. This was consistent with the analysis of Cole–Cole plots in rheological properties.…”
Section: Resultsmentioning
confidence: 99%
“…A análise termomecânica pode ser utilizada para avaliar a compatibilidade dos sistemas poliméricos de forma semelhante às propriedades mecânicas (ARAÚJO et al, 2004) (TAKEMORI et al, 1979;LUNA et al, 2015;BIRUDUGADDA et al, 2016;LUNA et al, 2018) A Figura 11 ilustra a fotomicrografia obtida por MEV da superfície de fratura das blendas compatibilizadas, com um aumento de 5000x.…”
Section: Temperatura De Amolecimento Vicatunclassified
“…Thus, some recent studies were reported in the literature about the development of polymer blends based on rubber waste and polystyrene . Most of the published papers deals with the reuse of rubber waste tire and no paper was found exploring the influence of the mixing sequence of twin screw extruders.…”
Section: Introductionmentioning
confidence: 99%